THE CORRELATION BETWEEN DIET AND THE TYPE OF CANCER AT THE CHEMOTHERAPY ROOMS IN GENERAL HOSPITAL ABDUL WAHAB SJAHRANIE SAMARINDA - Rini Ernawati; Niswatun Amanah (Universitas Muhammadiyah Kalimantan Timur, 2019)
Cancer is an abnormality in the body organs, for instance the abnormal cells grow very quickly, and consequentlydisrupt the performance of normal cells. An unhealthy meal pattern can cause cancer and stress and in long term it can cause thedecrease of immunity, as the result someone with low immunity is at risk to get sick easily.The purpose of the research was toidentify the correlation between diet and the type of cancer at the chemotherapy rooms in General Hospital Abdul Wahab Sjahranie.This study employed quantitative research design with cross sectional approach. The number of the population in this research was 183 respondents and 125 samples were selected to participate with purposive random sampling technique. The instruments of meal pattern questionnaire is used to collect the data and Chi-Square test was utilized to analyse the statistics test.The finding from the correlation between the variable of meal pattern and the type of cancer showed significant result pvalue = 0.003 a<0.05. This means that there was significant correlation between diet and the type of cancer. This result indicate that is significant influence between meal pattern with the type of cancer